Food Safety, Sufficiency, and Security - Crawford, Lester M.; Cleberg, Harry D.; Schwecke, Warren M.; Lineback, David R.; Nelson, John H.; Fogleman, Ralph W.; Lechtenberg, Victor L.; Stuckey, Richard E. (Council for Agricultural Science and Technology (CAST), 1998)
New and changing circumstances require examination of policy options by governments, agribusinesses, food producers and processors, and consumers. In response to this need, CAST sponsored a November 1997 conference to explore the complex relationships among food safety, sufficiency, and security on a global and U.S. basis. This Special Publication contains the proceedings of the conference as well as a general summary of challenges and solutions for the future.